Creation of Beta Crystal Structure in Random Polypropylene with the Help of Pimelic Acid-Based Nucleator: the Role of Nucleator Addition Method and the Presence of Isotactic Polypropylene in the Composition - H. Ghorbani; R. Bagheri (Journal of Advanced Materials in Engineering)
Compared to block copolymer, random polypropylene copolymer has lower toughness and impact resistance. This defect creates limitations in the use of this polymer in some applications such as pipe industry. Creating a beta crystal structure in random polypropylene with the help of nucleating agent is a well-known method to solve this problem. In this research, two types of nucleating agent were used to create a crystal structure, namely pre-synthesized pimelic acid nucleating agent and in-situ synthesis of pimelic acid during processing (0.2% by weight). Also, 4 wt.% isotactic polypropylene was added to increase the efficiency of nucleation. The goal was to compare the effectiveness of isotactic polypropylene with two types of nucleating agents.The samples needed for the tests were produced by compression molding method. Crystal structure evaluation was done by differential scanning calorimetry and X-ray diffraction methods. A transmission optical microscope  was employed to examine the microstructure of the samples. Tensile and impact tests were performed to examine the mechanical behavior of the samples. According to the differential scanning calorimetry and X-ray diffraction tests, it was observed that the sample made by adding 4 wt. % isotactic polypropylene has the highest amount of beta phase (67 and 72% in each test, respectively). Microscopic images also clearly showed the collapse of the structure due to the increase in beta phase. Also, according to the purpose of the research, the aforementioned sample revealed a 100% increase in toughness compared to the pure sample.